Entre experimentações e experiências: desafios para o ensino das competências para a promoção da saúde na formação do enfermeiro - Kênia Lara da Silva; Bárbara Jacome Barcelos; Bruna Dias França; Fernanda Lopes de Araújo; Izabela Thaís Magalhães Neta; Michelle Melo Ledo (Faculdade de Medicina de Botucatu (Unesp), 2018)
The aim of this study was to analyse the teaching of competencies for health promotion in Nursing Education and to identify experimentations and experiences in this process. It was a qualitative whose data were collected in focus groups with teachers and students from 11 undergraduate nursing courses in Brazil. The results showed that health promotion competencies are temporally taught in the contact and interaction with reality through experimentations and experiences. Experimentation is an event determined by a specific place and time in the course, while experiences are related to a meaningful discovery and an opening to the unknown. The challenge to the teaching of competencies for health promotion is that it should overcome the logic of experimentation, which is structured on technical rationality, and favour a perspective that allows and values experiences in Nursing education.